The Problems of Discourse Markers and Coherence in the Graduate’s Theses of Sintuwu Maroso University - Yuliana Dg Macora (Sintuwu Maroso Journal of English Teaching, 2016)
The present study went under the issue of discourse markers (hereafter DMs) as text forming devices in English discourse. This topic selection as an object of investigation was motivated by some facts. Firstly, this linguistics item was seldom taught specifically to students in lecturing, so students only know a few of English DMs. Secondly, in the last three decades, researches on developing the theory of DMs as a text forming devices were reinvestigated for many types of text, which previously only a cursory examination. Lastly, these items did not have a uniform system in the former researches. They have the distinction of correlation between propositional meaning and contextual meaning as well as other factors . This study aimed to investigate the problems of discourse markers usage in build coherence in the graduates’ these of English Education Study Program of Sintuwu Maroso University. The data were taken from the Background section of Chapter I of the 5 sellected graduates’ theses as the sample of the study. The result of this research revealed that the graduates could employ the four types of DMs in their theses, although there are some markers were not included in Fraser’s theory (1999, 2009), for instance if, such as, as well as, like, for, so that, and as. The result of analysis also showed that the lack, the misplacement and the inappropriateness ofusing DMs indeed affected the flow of graduates’ theses writing and made them less coherent.Keywords: discourse markers, coherence, thesis